On the Spatial Locality of Electronic Correlations in LiFeAs - Kim, Minjae; Hu, Miao; Choi, Sangkook; Zingl, Manuel; Georges, Antoine; Kotliar, Gabriel (arXiv.org, 2021)
We address the question of the degree of spatial non-locality of the self energy in the iron-based superconductors, a subject which is receiving considerable attention. Using LiFeAs as a prototypical example, we extract the self energy from angular-resolved photoemission spectroscopy (ARPES) data. We use two distinct electronic structure references: density functional theory in the local density approximation and linearized quasiparticle self consistent GW (LQSGW). We find that with the LQSGW reference, spatially local dynamical correlations provide a consistent description of the experimental data, and account for some surprising aspects of the data such as the substantial out of plan dispersion of the electron Fermi surface having dominant xz/yz character. Hence, correlations effects can be separated into static non-local contributions well described by LQSGW and dynamical local contributions. Hall effect and resistivity data are shown to be consistent with this description.